The Effect of Institutional Ownership, Sales Growth, Firm Size on Tax Avoidance with Corporate Social Responsibility as a Moderating Variable - I Kadek Dedy Suryatna; Desak Nyoman Sri Werastuti; Gede Adi Yuniarta (International Journal of Social Science and Business, 2023)
Tax avoidance practices are one of the causes of reduced tax revenue from predetermined projections. This study examines whether companies in Indonesia will engage in tax avoidance practices when they start implementing CSR. Thus, this study aims to describe the magnitude of the influence of institutional ownership, sales growth, company size in the trade, services, and investment sectors of companies listed on the Indonesia Stock Exchange on corporate tax avoidance by adding corporate social responsibility as a moderate variable. The sample of this study was selected based on predetermined criteria. The purposive sampling method was used to obtain 31 companies in the trade, services and investment sectors listed on the Indonesia Stock Exchange for 2017-2021. Data from the company's financial and annual statements are then analyzed using Eviews software. The findings revealed that institutional ownership and firm size positively influence tax avoidance; However, sales growth negatively impacts tax avoidance. Corporate social responsibility disclosures can moderate and weaken the effect of sales growth on tax avoidance. However, it strengthens the link between institutional ownership and company size on tax avoidance. The implication is that there needs to be stricter regulatory action and attention to transparency and good tax reporting in order to achieve fairer and more sustainable taxation.